Technology-enhanced learning (tel) of number systems - Zhang, Yue Jun (2017)
Technology-Enhanced Learning (TEL) is a new way to learn NTU’s full qualification programme courses without the constraints of place and time. For this project, the focus is on the specific area Number Systems from the module EE2004 Digital Electronics of the School of Electrical and Electronics Engineering.